Association between the triglyceride/high-density lipoprotein (TG/HDL) ratio and incidence of gout: A nationwide cohort study - Chang, Yoonkyung; Park, Ju-young; Song, Tae-Jin (Frontiers in Endocrinology, 2025)
IntroductionThe global burden of gout, a severe and painful arthralgia, is of note and is expected to increase in the future. We aimed to investigate the association between the triglyceride/high-density lipoprotein (TG/HDL) ratio, a simple and validated biomarker for insulin resistance, and the incidence of gout in a longitudinal setting in the general population.MethodsOur study was conducted using the National Health Insurance Service-Health Screening Cohort database of Republic of Korea (2002–2019). We included 300,107 participants who had no previous history of gout and had data for more than three repeated measurements of the triglyceride-glucose (TyG) index. The incidence of gout was determined using at least two or more claims of the ICD-10 code M10.ResultsDuring a median 9.62 years (interquartile range 8.72–10.53), 14,116 individuals (4.72%) had a reported incidence of gout. In a fully adjusted multivariable time-dependent Cox proportional hazards model with repeated measures of the TyG index, a unit increase in the index significantly increased the risk of gout in the entire cohort (hazard ratio (HR) = 1.150, 95% confidence interval (CI) 1.116–1.184). In a multivariable Cox proportional model of average TyG index quartiles, comparison of the lowest (Q1) and highest quartiles (Q4) indicated a significant positive association with the incidence of gout (HR: 1.326, 95% CI: 1.260–1.397). This association was non-linear (J-shape) when assessing the entire cohort and the diabetes and non-diabetes cohorts.ConclusionOur study demonstrated that increased TyG index was associated with an incidence risk of gout in the general population. Additionally, this association was non-linear (J-shape) not only in the entire cohort, but also in diabetes mellitus and non-diabetes mellitus cohorts. The TyG index may be an important predictor of gout.